1988
DOI: 10.1016/s0022-5347(17)42526-2
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of Methods to Produce Intrascrotal Testicular Fixation

Abstract: Methods to produce fixation between the tunica albuginea (visceral tunica vaginalis) and surrounding structures were used in Sprague-Dawley rats as an experimental model of orchiopexy to prevent testicular torsion. Eversion of the parietal tunica vaginalis without suture, or with absorbable or nonabsorbable suture produced excellent scarification, as did the use of talc. Absorbable and nonabsorbable suture, when placed between the parietal tunica vaginalis and tunica albuginea (visceral tunica vaginalis), prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 18 publications
2
10
0
2
Order By: Relevance
“…In fact, experimentally, when the tunica vaginalis is everted, scarification had similar efficacy to suture fixation. 35 As noted previously, in another experimental model, Ribeiro et al demonstrated that suture testicular fixation resulted in adverse histological consequences. 16 In a clinical study of 22 men who underwent prepubertal orchiopexy with chromic testicular fixation, US demonstrated tunica albuginea calcification in 32% and subtunical hypoechogenicity in 14%.…”
Section: Transparenchymal Suture Fixationmentioning
confidence: 60%
“…In fact, experimentally, when the tunica vaginalis is everted, scarification had similar efficacy to suture fixation. 35 As noted previously, in another experimental model, Ribeiro et al demonstrated that suture testicular fixation resulted in adverse histological consequences. 16 In a clinical study of 22 men who underwent prepubertal orchiopexy with chromic testicular fixation, US demonstrated tunica albuginea calcification in 32% and subtunical hypoechogenicity in 14%.…”
Section: Transparenchymal Suture Fixationmentioning
confidence: 60%
“…Our technique of orchidopexy offers the combined advantages of eversion of the tunica vaginalis, which has been shown previously to produce excellent fixation to the scrotal wall and avoidance of injury to testicular parenchyma, whilst offering an additional protection from re‐torsion in the form of non‐absorbable sutures through the tunica vaginalis into the posterior scrotal wall. There is also an additional benefit of perceived reduced scrotal discomfort after surgery, as chronic irritation of tunica albuginea by sutures is avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Rodriguez and Kaplan carried out a similar study, re‐exploring the testes at 30 days 16 . However, instead of creating a window in the tunica vaginalis, the tunica vaginalis was completely everted and sutured behind the testis, as in the Jaboulay hydrocele repair, without any testicular fixation sutures.…”
Section: Techniques To Produce Testicular Fixationmentioning
confidence: 99%